L' état de la planète : 1991 - Brown, Lester R.; Flavin, Christopher; Postel, Sandra; Starke, Linda (Paris : Economica, 1991)
Bibliotheek François Vercammen
Nederlands
Monografie
Keywords: milieuvervuiling; milieu; internationale samenwerking